Robustness analysis in forward modelling gravity data in crustal/lithospheric studies - POHÁNKA, Vladimír; VAJDA, Peter; BIELIK, Miroslav; DÉREROVÁ, Jana (Contributions to Geophysics and Geodesy, 2011)
The robustness of the gravimetric forward modelling is investigated by applyingthe harmonic inversion procedure at the input which is the difference of the calculatedand measured surface gravity. The gravity data are taken from two profiles inthe Carpathian-Pannonian Basin region. The result of the inversion are density modelsobtained from the original two-layer models with various horizontal boundary depth anddensity contrast. The deformation of the originally planar boundary is the measure ofthe mismatch between calculated and measured data. The calculated deformation hasreached up to tens of kilometers and thus the uncertainties in determining the geometryof disturbing bodies by the forward modelling are substantial.